FAKTOR-FAKTOR YANG BERKORELASI DENGAN KUNJUNGAN BALITA KE POSYANDU PADA IBU DENGAN ANAK USIA DI BAWAH SATU TAHUN - Arikhman, Nova (Jurnal Ipteks Terapan, 2011)
The purpose of this research is to find out the correlated faktors with the visit of the children under five to Integrated-Service Post in which consist of mother’s knowledge about Integrated-Service Post, character of cadre, and support of family.  Part of population is taken as research respondents, technique sampling by means of cluster random sampling are 180 mothers who have the children under five.  To collect data, the researcher uses questioners and furthermore, they analyzed with chi-square, univariat and bivariat analyses.Based on the data analyses, it is found that less visiting to Integrated Post are 80,4%,  and high knowledge of mothers are 81,7%, less having a role of cadres are 77,8%, and beside that, low supporting of family are 51,1%.  The statistical analysis indicates that, there is significant all correlated faktors with the visit to Integrated Service Post, the correlation of family tendency is low with the exception of knowledge.  Thus, these cases resulted in minus information about the schedule of Integrated Service Post.  On the bases of the research findings, it is recommended to the local health staff should do their activity of Integrated Service Post on time, neither routine schedule nor time of activity.